Influences of buffer systems on enzymatic saccharification of rice husk holocellulose and fermenting ability of various ethanol producing microorganisms - Woottichai Nachaiwieng (2018)
© 2017, Chiang Mai University. All rights reserved. Four saccharification buffers, including acetate, citrate, phthalate and succinate buffers, were evaluated for their effects on both saccharification and fermentation of rice husk holocellulose. At a concentration of 30 mM, all buffer systems were found to be suitable for saccharification by three commercial cellulolytic enzymes (Meicelase, Accellerase 1500 and Accellerase XC). However, at concentrations of 50-200 mM, citrate and acetate buffers partially inhibited the fermenting ability of Saccharomyces cerevisiase, Zymomonas mobilis, Kluyveromyces marxianus, Candida shehatae and Pichia stipitis. This was in contrast to phthalate and succinate buffers in which these organisms retained 100% relative fermenting ability within concentrations in the range of 50-500 mM. This is the first report indicating potential buffers appropriate for broad ethanol producing microorganisms in bioethanol fermentation, particularly for co-culture fermentation of cellulosic hydrolysate.